Improved multicast routing in MANETs using link stability and route stability. (1st December 2016) - Singal, Gaurav; Laxmi, Vijay; Rao, Vijay; Todi, Swati; Gaur, Manoj Singh
Summary: The growing popularity of multimedia applications and services needs to support several quality of service metrics such as high throughput, low energy, and jitter, which is a challenging task in mobile ad hoc networks. Because of limited bandwidth, energy constraints, dynamic topology, transmission errors, and fluctuating link stability, the links between adjacent nodes are often not reliable and may break because of node mobility. Link breakage initiates the process of rerouting either at the sender node (the node at which the link breaks) or at the source node. In either case, it leads to packet loss, delivery delays, and increased control overheads. Hence, to attain a minimum quality of service, routing protocols must address the dynamic network topology. Uncertain and varying movement of nodes necessitates stability of the links between such nodes. The objective of this paper is to propose 2 protocols, the first based on link stability and the other based on route stability. Link stability identifies a stable link from the available links to the next hop and determines a stable end‐to‐end route. The probability of successful transmission of periodic packets is used as a link stability metric to assess the stable path. Acknowledgment ‐free packets are used to check connectivity in the network. Increased probability of successful transmission implies that the selected link is sustained for longer duration and can deliver packets more reliably or, as a consequence, results in a stable link to deliver a better data rate. With a stable link, there is a reduced possibility of retransmissions, reduced end‐to‐end delay, reduced control overheads, and enhanced data delivery ratio. Selection of the most stable route for data transmission improves the performance. Experimental results from simulations performed on EXata/Cyber v2.0 simulator reveal that our proposed protocols are an improvement over the existing protocols in terms of packet delivery ratio, average end‐to‐end delay, and average route lifetime, even without route optimization with the minor increase in control packets. A case study of the application of proposed protocols is also presented. Abstract : Link breakage initiates the process of rerouting at the source node. It leads to packet loss, delivery delays, and increased control overheads. The objective of this paper is to propose protocols based on link stability and route stability. The probability of successful transmission of periodic packets is used as a link stability metric to assess the stable path. Increased probability of successful transmission implies that the selected link is sustained for a longer duration and can deliver packets more reliably.